2010
DOI: 10.1126/scitranslmed.3001305
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser–Assisted Cataract Surgery with Integrated Optical Coherence Tomography

Abstract: About one-third of people in the developed world will undergo cataract surgery in their lifetime. Although marked improvements in surgical technique have occurred since the development of the current approach to lens replacement in the late 1960s and early 1970s, some critical steps of the procedure can still only be executed with limited precision. Current practice requires manual formation of an opening in the anterior lens capsule, fragmentation and evacuation of the lens tissue with an ultrasound probe, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
194
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(204 citation statements)
references
References 38 publications
3
194
0
3
Order By: Relevance
“…Each laser incision is constructed in the posteroanterior plane, a principle that elegantly employs the posterior microcavitation bubbles to scatter the laser beam and reduce the amount of energy reaching the Laser-assisted cataract surgery S Trikha et al retina. 14 By keeping the bubbles posterior to the laser target, the focus of the laser beam is maintained and this avoids scatter before the target tissue. 14 The sequence of incision creation varies between the available FLACS platforms and although theoretical differences exist, there is currently insufficient evidence to suggest which order has superiority.…”
Section: Intraoperative Anterior Segment Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Each laser incision is constructed in the posteroanterior plane, a principle that elegantly employs the posterior microcavitation bubbles to scatter the laser beam and reduce the amount of energy reaching the Laser-assisted cataract surgery S Trikha et al retina. 14 By keeping the bubbles posterior to the laser target, the focus of the laser beam is maintained and this avoids scatter before the target tissue. 14 The sequence of incision creation varies between the available FLACS platforms and although theoretical differences exist, there is currently insufficient evidence to suggest which order has superiority.…”
Section: Intraoperative Anterior Segment Imagingmentioning
confidence: 99%
“…To a certain extent, it can also transmit through optically denser media such as oedematous or mildly opacified cornea. 13,14 This permits precise focusing of a 3 mm spot, accurate to within 5 mm inside the anterior chamber. 12 Second, although argon, excimer, and Nd:YAG lasers involve nanosecond (10 À 9 s) pulses, the Nd:glass FSL employs an ultrafast pulse time of 10 À 15 s. This allows far smaller amounts of energy to be used while maintaining similar power output.…”
Section: Flacs: Physiology and Mechanicsmentioning
confidence: 99%
“…OCT-guided laser surgery has been developed for use in ophthalmic surgery (97,98). Boppart et al reported that it is a new approach, where the integration of real-time highresolution OCT and laser ablation can realize the treatment of brain tumors in vivo and in situ; the system could image the dynamic changes before, during, and after intraoperative laser ablation scenarios (30).…”
Section: Integrated Oct and Laser Ablation System For Realtime Treatmmentioning
confidence: 99%
“…2,11,12,19 The unpredictable diameter observed in manual capsulorhexis may lead to an irregularly shaped capsulotomy and influence the position of the implanted IOL, which may cause a decrease in visual quality. 20 Capsulotomies created during FLACS were more regularly shaped than those in manual capsulorhexes, with better centration, and better IOL/capsule overlap compared with manual capsulorhexes.…”
Section: Capsulotomy Accuracy and Precisionmentioning
confidence: 99%
“…9 The capsular openings created in FLACS have increased strength and rupture force compared with those in manual capsulorhexis in cadaveric eyes. 2,[10][11][12] This may reduce the incidence of intraoperative tears to the capsular bag, a source of complications in cataract surgery. Initial data on FLACS suggest an incidence of anterior tears of 0.2 %.…”
Section: Capsulotomy Strengthmentioning
confidence: 99%